The effect of contextual and interfering factors on the development of sports and physical activity in children - Maryam Aziziani; Asra Ershad; Ahmad Mahmoudi; Saman Mehri (Sport Sciences and Health Research)
Background: Sports and physical activity are important for the healthy growth and development of children. However, various contextual and interfering factors can hinder the development of sports and physical activity in children.  Aim: The purpose to identify the contextual and interfering factors affecting the development of sports and physical activity in children.Material and Methods: The present study adopts a combinatory approach, where the first stage is qualitative and exploratory, and the second stage is descriptive-survey. In the qualitative stage, 16 experts in the field of children's sports were interviewed using purposive sampling, and the collected data were analyzed using MAXQDA 2020 software. In the quantitative stage, SPSS software version 26 was used for exploratory factor analysis and t-tests, while PLS 3 software was used for confirmatory factor analysis.Results: The results of this study suggest that there are five contextual factors-personal and family, infrastructure and equipment, supportive, economic and managerial as well as five interfering factors-human resources, organizational, media activities, control and evaluation, and legislation. Furthermore, the results of confirmatory factor analysis indicated that the research measurement model was validated.Conclusions: In conclusion, it can be acknowledged that by considering the identified factors in the development of sports and physical activity in childhood, it is possible to address some of the challenges in the field of children's sports.